Perkembangan Teknologi Sebagai Modus Scamming Di Laman Jual Beli Online - Retno Wahyu Ningsih; Robi’ah Al Adawiyah; Andhita Risko Faristiana (Jurnal Kajian dan Penelitian Umum, 2023)
Indonesia is one of the countries with rapid technological developments. Through the development of this technology, of course, it will make it easier for the community to carry out activities, such as buying and selling online. Buying and selling online is very popular in the community, because for them it is very easy, fast and practical. However, along with the convenience that is presented in buying and selling online, it is often used by irresponsible persons to seek profit. The research method used is a qualitative research method. The main focus of this research is to see the reality that occurs in the field with the aim of digging up information about fraud in buying and selling and the laws that are applied. Researchers use this research because they want to clearly describe the technological developments that are used as a fraudulent mode of buying and selling online.